Development of Community-Based Tourism in Pinusan Kragilan, Pogalan Village, Magelang Regency, Central Java, Indonesia - Sasongko, Gatot; Trianggono, Bagus; Wiloso, Pamerdi Giri (Journal of Indonesian Tourism and Development Studies, 2019)
The purpose of this study is to describe community involvement in the development of Kragilan Top Selfie Pinusan tourist destinations (TSPK) and explain the role of Tourism Awareness Groups (Pokdarwis) in developing TSPK tourist destinations. This study uses the concept of Community-Based Tourism (CBT) as an analytical framework. The method used in this study is a qualitative research method. Data collection techniques were carried out by observation, documentation, and in-depth interviews with parties related to TSPK tourist destinations. The results of the study indicate that community participation in the process of developing the TSPK was encouraged by the local community namely Pokdarwis (tourism-aware group). Pokdarwis, in this case, plays a role in the division of labor; financial management; and managing cleanliness. Pokdarwis conducts division of labor to encourage community participation. The forms of community participation in TSPK include workforce and the contribution of ideas in developing TSPK. Next, the existence of TSPK also empowers the economy of the people in Kragilan Hamlet. Pokdarwis also empowers the community to manage the environment around the destination. Then TSPK shows that the CBT model that is different from CBT in general, in TSPK empowerment is carried out independently by Pokdarwis. Only after Pokdarwis initiated this empowerment and brought economic benefits, the government (Gunung Merbabu National Park Office) took part in helping TSPK management.Keywords: Community Based Tourism (CBT); Community Engagement; Participation; Top Selfie Pinusan Kragilan (TSPK).